Pediatric anaphylactic adverse events following immunization in Victoria, Australia from 2007 to 2013. Issue 13 (24th March 2015) - Cheng, Daryl R.; Perrett, Kirsten P.; Choo, Sharon; Danchin, Margie; Buttery, Jim P.; Crawford, Nigel W.
Highlights Anaphylaxis as an adverse event following immunization (AEFI) is a rare but important diagnosis. This is due to associated morbidity risk and implications for future vaccinations. Diagnostic criteria for anaphylaxis are difficult to implement in a passive AEFI surveillance system. All cases of anaphylaxis in this Australian case series had no long-term sequelae.